The Influence of Income, Social Capital, and Participation in Farmer Group on the Sustainability of Vegetable Farmers Business in Selo Village Selo Sub-district Boyolali Regency - Zulpicha, Empratikta; Slamet, Yulius; Wijaya, Mahendra (Advances in Social Sciences Research Journal, 2019)
This study aimed to explain how much income and social capital influenced the sustainability of vegetable farmer businesses in Selo Village, Selo District, Boyolali Regency. This study used quantitative research with survey methods. The population in this study was 584, thus the samples that taken were 123 respondents with 8% error rate. The researchers got the sources of data from the results of questionnaires which were distributed to vegetable farmers in Selo village and supported by data from the Selo village. Questionnaires used as data collection techniques and multiple linear regression analysis used as data analysis techniques in this study. The results of this study showed that there is an influence of income and social capital on business continuity. It was known that the significance value of the income variable (X1) was 0,000 and social capital (X2) was 0,000. It can be concluded that income variables (X1) and social capital (X2) significantly influenced the business continuity variable (Y) because the significance value is smaller than 0.05. The value of R2 or R Square is 0.225, this indicated that the contribution of the influence of X1 and X2 on Y is 22.5% while the remaining 77.5% is the contribution of other variables which were not examined.